Medicamentos potecialmente inapropriados para idosos: da seleção à prescrição na atenção primária à saúde - Farias, Andrezza Duarte (2021)
Population aging is a growing reality, and the elderly need medications, which often expose them to risks. Potentially inappropriate medications (PIMs) in the elderly are those in which risks outweigh benefits. Essential medications must meet health needs of a population, and medication prescription is one determinant for its use. This study aimed to analyze PIM in the elderly from the selection of essential drugs to prescription in primary health care (PHC). A descriptive and analytical study with quali-quantitative approach was conducted in PHC in Campina Grande (PB) between March and December 2019. The study was developed triangulating methods: 1) documentary research, which analyzed medicines of the National Essential Medicines List (RENAME) in 2010 and 2020 editions according to AGS/Beers criteria and essential medicines lists (EML) of the World Health Organization; 2) crosssectional study, conducted using interviews with 458 elderly users of 71 basic health units. Independent variables were demographic and socioeconomic characteristics, health condition, and use of medication, whereas the dependent variable was prescribed medication classified as inappropriate by the Brazilian Consensus on Potentially Inappropriate Medications. Descriptive data analysis and Poisson regression were performed; and 3) case study, using interviews conducted with 10 PHC prescribers to observe perception of these professionals regarding prescription for the elderly. One thousand four hundred and forty-nine medications and 244 PIM (16.8%) were prescribed; of these, 91.6% and 70.5% were listed in RENAME, respectively. Most PIM acted in the central nervous system (54.4%) and gastrointestinal tract and metabolism (20.1%). RENAME lacked safer therapeutic alternatives for main PIMs. In the cross-sectional study, at least one PIM was prescribed for 44.8% (95%CI 40.2 ˗ 49.3) of the elderly. In the adjusted model, depression (PR=2.01; 95%CI 1.59 ˗ 2.55), use of medication other than those prescribed (PR=1.36; 95%CI 1.08 ˗ 1.72), and polypharmacy (PR = 1.80; 95%CI 1.40 ˗ 2.33) were associated with PIM, whereas self-reported hypertension was a protective factor (PR=0.65; 95%CI 0.49 ˗ 0.87). Two categories emerged in the qualitative analysis: 1) approach of prescribers to assist the elderly in PHC and 2) use of medication by the elderly: view of prescribers. Doctors reported preventive activities but emphasized treatment of prevalent chronic diseases among the elderly. They also highlighted polypharmacy and considered benzodiazepines to be inappropriate. Doctors lacked knowledge about inappropriate medication lists. Medicalization of the elderly and availability of essential medication were described as challenges. PIMs were highly prescribed for the elderly in PHC according to the RENAME and safer therapeutic alternatives were absent. Actions to qualify access of the elderly to medication are needed, such as elaborating a specific list of medication, inserting safer therapeutic alternatives for the elderly in RENAME, training prescribers, and monitoring the elderly. Access to medication and safety of the elderly must be guaranteed because of aging of the Brazilian population.